Sprint and distance swimmers: The same animal? - McCabe, C. B. (Applied Swimming Programme Schedule - 27th International Conference on Biomechanics in Sports, 2009)
In this talk the techniques of sprint and distance swimmers are discussed with a view to informing coaches of the similarities and differences between these groups. In the past it has been reported that sprint and distance swimmers are different in several aspects of technique. However, previous comparisons were at the respective race pace and sprint and distance specialists have not been compared when swimming at the same pace. Therefore it is difficult for coaches to know whether to teach the swimmers the same way when developing good technique. This talk presents new information based on recent scientific research conducted at the Centre for Aquatics Research and Education (CARE). The variables of interest were: average swim speed, stroke length, stroke frequency, stroke index, hand stroke pattern, foot range of motion, elbow angle, shoulder and hip roll angle and stroke phase durations. Interesting and unexpected findings emerged that have implications for the way specialist sprint and distance swimmers should be coached.